P53-dependent upregulation of miR-16-2 by sanguinarine induces cell cycle arrest and apoptosis in hepatocellular carcinoma. (10th September 2019) - Zhang, Beilei; Wang, Xinan; Deng, Jiacong; Zheng, Haifeng; Liu, Wei; Chen, Si; Tian, Jie; Wang, Fu
Abstract: MicroRNAs (miRNAs) were involved in cancer progression, and the targeting of miRNAs by natural agents has opened avenues for cancer treatment and drug development. miR-16 functions as a tumor suppressor and is frequently deleted or downregulated in various human cancers, including hepatocellular carcinoma (HCC). In the present study, we employed a miR-16-responsive luciferase reporter to screen candidate compounds that modulate miR-16 expression from a natural product library. One compound, sanguinarine (SG), was capable of activating miR-16 in HCC cells with wildtype or mutated p53 expression but not in p53-deleted HCC cells. Mechanistic investigations revealed that SG increased p53 occupancy on the miR-16-2 promoter and decreased the expression of miR-16 target genes, including Bcl-2 and cyclin D1. Moreover, SG significantly inhibited HCC cell proliferation in a p53-dependent manner by inducing cell cycle arrest and reactive oxygen species (ROS)-associated apoptosis. Silencing miR-16 by treatment with anti-miR16 miRNA inhibitors rescued the cell viability repression effect caused by SG. Importantly, SG dramatically suppressed tumor growth in an HCC xenograft model, with little cytotoxicity. Taken together, our results provide a preclinical proof-of-concept for SG as a potential strategy for HCC treatment based on the restoration of miR-16 tumor suppressor function. Highlights: Sanguinarine upregulated miR-16 expression and downregulated its targets. Sanguinarine increased p53 occupancy on miR-16 promoter. Sanguinarine inhibited HCC cell proliferation in a p53 dependent manner. Sanguinarine induced-apoptosis is associated with ROS production. Sanguinarine dramatically suppressed HCC xenograft tumor growth.